2001
DOI: 10.1080/00221320109597485
|View full text |Cite
|
Sign up to set email alerts
|

Gender Segregation in Childhood: A Test of the Interaction Style Theory

Abstract: The authors investigated the play/interaction-style theory of gender segregation with a sample of 39 children aged 2 to 5 years (primarily Caucasian). According to this theory, children prefer playmates with styles of play or interaction that are similar to their own. Because such styles are sex differentiated, same-sex playmate preference (i.e., gender segregation) results. The authors observed children during free play to determine preferred playmates and gender segregation level, and they used teacher ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 33 publications
3
24
1
Order By: Relevance
“…Knudson and Kagan (1982) also used this principle in a questionnaire probing prosocial behavior. This approach is consistent with the gender segregation that occurs in childhood (e.g., Hoffmann, 2001;Wu, Zhou, Wei, & Bao, 2013). In other words, one major difference between the adult and child versions is that we introduced gender into the items in the French version for children.…”
Section: Basic Empathy Scale In Children (Bes-c)supporting
confidence: 53%
“…Knudson and Kagan (1982) also used this principle in a questionnaire probing prosocial behavior. This approach is consistent with the gender segregation that occurs in childhood (e.g., Hoffmann, 2001;Wu, Zhou, Wei, & Bao, 2013). In other words, one major difference between the adult and child versions is that we introduced gender into the items in the French version for children.…”
Section: Basic Empathy Scale In Children (Bes-c)supporting
confidence: 53%
“…In support of this contention, observational studies of preschool children have shown that boys engage in more vigorous-intensity activities, play in larger groups in more open settings, engage in more risk-taking behavior, and play rougher games involving greater amounts of body contact than girls. [26][27][28] While it is not possible to provide a definitive explanation for our gender-specific findings, the large gender gap in physical activity observed in this and other studies of preschool children, 29-31 strongly supports the recommendation that efforts to promote physical activity in girls start early in life. 32,33 Recent research has shown that familial patterns of overweight and obesity are mediated, in part, by parenting eating behaviors (parental energy intake, mother's dietary restraint, and disinhibition) and parental child-feeding practices (concern for child's weight, monitoring, and restriction of child's food intake).…”
Section: Discussionmentioning
confidence: 48%
“…In support of this contention, observational studies of preschool children have shown that boys engage in more vigorous-intensity activities, play in larger groups in more open settings, engage in more risk-taking behavior, and play rougher games involving greater amounts of body contact than girls. [26][27][28] While it is not possible to provide a definitive explanation for our gender-specific findings, the large gender gap in physical activity observed in this and other studies of preschool children, [29][30][31] strongly supports the recommendation that efforts to promote physical activity in girls start early in life. 32,33 Recent research has shown that familial patterns of overweight and obesity are mediated, in part, by parenting eating behaviors (parental energy intake, mother's dietary restraint, and disinhibition) and parental child-feeding practices (concern for child's weight, monitoring, and restriction of child's food intake).…”
Section: Discussionmentioning
confidence: 52%